РЕЖИМИ РОБОТИ БЕЗКОНТАКТНОГО МАГНІТОЕЛЕКТРИЧНОГО МЕХАТРОННОГО МОДУЛЯ ПРИ ДВОПРОВІДНОМУ УПРАВЛІННІ - Акинін, К.П.; Кіреєв , В.Г.; Пєтухов , І.С.; Філоменко, А.А. (Інститут електродинаміки Національної академії наук України, 2025)
The paper is devoted to the study of the characteristics and operation modes of the input rectifier in the structure of the mechatronic module based on a brushless AC motor with permanent magnets when two-wire control from a power source with pulse-width regulation of the sequence of rectangular voltage pulses. To reduce switching losses in the rectifier MOSFETs, it is proposed to introduce additional differentiating RC circuits into the gate circuits. The influence of the parameters of these RC-circuits on the value of switching losses in transistors is studied. Preliminary values of these parameters for minimization of switching losses are obtained. Dependences of losses in transistors and rectifier efficiency on the value of load current are obtained. A comparison of rectifiers based on MOSFETs and Schottky diodes is carried out.